Special study on sustainable fisheries management and international trade in the Southeast Asia and Pacific region - Masayuki Komatsu (Asian Development Bank Institute (ADBI), 2013)
This paper analyzes the current status of fisheries and aquaculture in Southeast Asia and international trade. Analysis concludes that a policy of sustainable management for both capture fisheries and aquaculture is of greatest importance, but such a policy has been neither planned nor implemented with a holistic and long-term perspective. Current policy reflects a short-term view and the immediate needs of each nation. Therefore, capacity building of human resources and organizations, including governments, is needed for the formulation of holistic national policies to seek long-term and fundamental remedies for the sustainable management of fisheries resources and intensified and extensive aquaculture. Such holistic national policies should include science-based management, monitoring, enforcement, coordination of capture fisheries and aquaculture, and international trade policies. It may include the effects of climate change and oil price increases, as well as international market trends and regulations or barriers. Moreover, international trade will be promoted based on the sustainability of capture fisheries and aquaculture. ADB members and governments are urged to provide official development assistance for policy implementation, in particular to the private sectors that may not otherwise receive any, and to small and community-related businesses. Recommendations focus on building capacity for the long run, among others, for which facilitation should be provided.
Keywords: F64; Q22; O13; 330; international trade; fisheries; development of natural resources; aquaculture southeast asia; Fischerei; Aquakultur; Fischschutz; Außenhandel; Südostasien